A deeper understanding of intestinal organoid metabolism revealed by combining fluorescence lifetime imaging microscopy (FLIM) and extracellular flux analyses. - Monaghan, Michael (My University, 2020)
Stem cells and the niche in which they reside feature a complex microenvironment with tightly regulated homeostasis, cell-cell interactions and dynamic regulation of metabolism. A significant number of organoid models has been described over the last decade, yet few methodologies can enable single cell level resolution analysis of the stem cell niche metabolic demands, in real-time and without perturbing integrity. Here, we studied the redox metabolism of Lgr5-GFP intestinal organoids by two emerging microscopy approaches based on luminescence lifetime measurement – fluorescence-based FLIM for NAD(P)H, and phosphorescence-based PLIM for real-time oxygenation. We found that exposure of stem (Lgr5-GFP) and differentiated (no GFP) cells to high and low glucose concentrations resulted in measurable shifts in oxygenation and redox status. NAD(P)H-FLIM and O2-PLIM both indicated that at high ‘basal’ glucose conditions, Lgr5-GFP cells had lower activity of oxidative phosphorylation when compared with cells lacking Lgr5. However, when exposed to low (0.5 mM) glucose, stem cells utilized oxidative metabolism more dynamically than non-stem cells. The high heterogeneity of complex 3D architecture and energy production pathways of Lgr5-GFP organoids were also confirmed by the extracellular flux (XF) analysis. Our data reveals that combined analysis of NAD(P)H-FLIM and organoid oxygenation by PLIM represents promising approach for studying stem cell niche metabolism in a live readout.
PUBLISHED
Keywords: Hypoxia imaging; Intestinal organoids; NAD(P)H; Optical metabolic imaging; Oxygen; Stem cells